A comparative study on the allelopathy and toxicity of four strains of Karlodinium veneficum with different culturing histories. (4th January 2019) - Yang, Huijiao; Hu, Zhangxi; Xu, Ning; Tang, Ying Zhong
Abstract: The dinoflagellate Karlodinium veneficum blooms kill fish by the production of karlotoxins. We investigated the allelopathy ( Akashiwo sanguinea as the target species) and toxicity ( Oryzias melastigma, Artemia salina and Brachionus plicatilis as test animals) of four strains of K. veneficum isolated from coastal waters of China and the USA to explore the ecological implications of allelopathy and toxicity. In general, all four strains of K. veneficum at high cell densities (>100 000 cells·mL −1 ) significantly inhibited the growth of A. sanguinea to different extents, but they exhibited either positive or negative allelopathy at lower densities. The toxicity of the four strains showed a decreasing order coinciding with their culture histories in the laboratory, suggesting K. veneficum may have gradually lost toxicity during laboratory culturing. The allelopathic and toxic potencies among K. veneficum strains were not perfectly parallel, indicating that either the allelochemicals and toxins of K. veneficum may be different chemicals, or the same chemicals functioned in different modes. Moreover, we found A. salina avoided feeding on more toxic strains. These results together suggest that toxins provide an advantage for K. veneficum via avoiding predation, but allelopathy may not play an important role in initiating blooms of K. veneficum .